HUKUM TOLERANSI KELOMPOK SALAFI TERHADAP KELOMPOK ISLAM LAINNYA DI KABUPATEN BANYUMAS - Rohman, Abdul; Puspitasari, Elis (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Islam as a religion has a doctrine full final, complete, comprehensive and universal, so that the texts that became the guiding principle is universally viewed as well. In the real level, especially in need of interpretation, often leading to problems of its own because each group has a flow that allows the results are different interpretations. This is like the Salafi group based its interpretation on groups considered heretical Islamic sects other, so that a constraint when a dialogue about the development of tolerance values. Despite the rejection of the dialogue is actually contrary to the Qur'an itself. Key words: Salafi, tolerance, interpretation, heretical innovation